2019
DOI: 10.1177/2516043519876756
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of patient safety culture among healthcare providers in the Upper East Region of Ghana

Abstract: Objective To find out the determinants of patient safety culture among healthcare providers in the Upper East Region of Ghana. Design This was a cross-sectional survey of three hospitals. The Hospital Survey on Patient Safety Culture questionnaire was adapted for data collection. Setting The setting was three selected hospitals (mission, public, and private) from the Upper East Region of Ghana. Participants A total of 393 healthcare providers were invited to participate, but 384 (98%) honored the invitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
6
5
0
Order By: Relevance
“…This indicates that even though each dimension measures a unique construct, at the same time it is related to a common underlying construct. This finding is consistent with the trend of relationship found in a similar studies in Ghana 28 and other countries. 24,29,30 Even though patient safety culture dimensions scores varied across participants' profession, Staffing and Non-Punitive Response to Errors were the only domains that differed significantly across professional groups (p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that even though each dimension measures a unique construct, at the same time it is related to a common underlying construct. This finding is consistent with the trend of relationship found in a similar studies in Ghana 28 and other countries. 24,29,30 Even though patient safety culture dimensions scores varied across participants' profession, Staffing and Non-Punitive Response to Errors were the only domains that differed significantly across professional groups (p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…This indicates that even though each dimension measures a unique construct, at the same time it is related to a common underlying construct. This finding is consistent with the trend of relationship found in a similar studies in Ghana 28 and other countries. 24,29,30…”
Section: Discussionsupporting
confidence: 93%
“…Even in the unlikely event that these adverse events occur, the commitment demonstrated by managers relative to safety-related issues would influence them to report with lessened fears or hesitation. A relatively higher rating score for management support for patient safety has been supported in recent studies by Abuosi, Akologo and Anaba, 34 corroborating the work of Khoshakhlagh et al 15 Elsewhere, studies have shown that when hospital management supports safety-related issues, there is an increase in adverse events reporting. 35,36 Other studies have reported that when management placed emphasis on patient safety and safety-related issues, there is a correlation with better safety outcomes and fewer incidences of adverse effect.…”
Section: Discussionmentioning
confidence: 53%
“…Other researchers have also reported higher rating scores for feedback about errors. 34,37 It is apparent therefore that when healthcare workers, including nurses, are given feedback promptly following reported adverse events, they would be motivated to report more of such incidences when encountered and, this would encourage them to inform others that are connected to the errors. The giving of feedback should usually be done in a timely manner by communicating relevant information about the incident and not dwelling on character or personality of the worker involved.…”
Section: Discussionmentioning
confidence: 99%
“…In Ghana, the Ministry of Health developed and launched Ghana’s National Healthcare Quality Strategy [ 22 ] however, the success of the implementation of such a strategy depends on the culture in the health establishments [ 23 25 ]. Patient safety studies in Ghana have found that teamwork and organisational learning are viewed as important dimensions to achieving patient safety culture [ 26 ]. While one study [ 5 ] found that management support had a significant relationship with patient safety culture in a teaching hospital in Ghana, a 2020 study in a teaching hospital found an extremely low rating on overall patient safety culture [ 5 ].…”
Section: Introductionmentioning
confidence: 99%